Perception and Performance of Youth Leadership of Kathmandu Metropolitan City - Kharel, Madan Kumar (KMC Research Journal, 2025)
The public perception and performance of youth leadership of Kathmandu Metro City is a mirror of youth leadership in the view of people. The main objective of the study is to find out the relationship between public perception and the performance of youth leadership. To probe the consequences, mixed method approach has been applied. Five-point Likert survey and qualitative interviews have been applied. In conclusion majority of people have perfectly positive perception and similar to the action or the performance of youth leadership. The correlation between perception and performance is 0.98, means the level of public perception and performance in Kathmandu is significant or satisfactory. Improving public perception of youth leadership can play a crucial role in enhancing the performance of youth leaders. Efforts to boost public perception should focus on transparency, community engagement, and addressing local concerns. This approach not only enhances the effectiveness of youth leadership but also fosters a positive feedback loop that benefits both the leaders and the communities they serve.